ANALISA DAN PERANCANGAN PENGEMBANGAN E-LEARNING DENGAN METODE DSDM (STUDI KASUS SDN 01 MANISREJO KOTA MADIUN) - Eva Puspitasari; Hani Atun Mumtahana; Ridho Pamungkas (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2023)
In digital era technology development and information growing so fast, so it can’t be denied for all aspects and especially in education already using technology to support activities. The world of education really need a technology and information to support learning activities to improve the quality better of learning, making it easier to interact teacher with student for learning resource sharing activities and sharing theory. E-Learning is a solution that can be used to support learning activities. So,in this research aims to develop E-Learning which is expected to help teacher and  students in managing class schedules, study material, quiz, attendance, and exam especially at SDN 01 Manisrejo Madiun City. The method using Dynamic System Development Method (DSDM) and UML for system design. From this study resulted in a proposed system analysis and design development system which can be developed into a complete system.